The ANALISIS PARAMETER QOS (QUALITY OF SERVICE) PADA JARINGAN WIFI DI GEDUNG FAKULTAS TEKNIK UNIVERSITAS JENDERAL ACHMAD YANI DENGAN MENGGUNAKAN WIRESHARK - Nicko Wahyudi; Atik Charisma; Hajiar Yuliana; Sofyan Basuki; Ade Sena Permana; Nivika Tiffany (EPSILON: Journal of Electrical Engineering and Information Technology, 2025)
WiFi performance is a pressing need in academic, especially to support learning, research, and communication. In the digital era, the demand for high network quality is increasing along with the heavy dependence on internet access for various academic activities. Therefore, the evaluation of the WiFi network quality in Jenderal Achmad Yani University is focus of this study, the network meets the required quality standards. This study uses a quantitative method with an observational approach to analyze the Quality of Service (QoS) parameters such as throughput, packet loss, delay, and jitter. The quantitative method was chosen because it is able to provide objective and accurately measured data, while the observational approach allows researchers to directly observe internet traffic and measure QoS parameters. Testing was conducted for three days to obtain representative data on the condition of the WiFi network in the building. From the test results conducted, it is known that the quality of the network in the Faculty of Engineering Achmad Yani University is: Average throughput of 1406.76 Kbps, packet loss of 0%, delay of 70.21 ms, jitter of 85.96 ms. With an average overall index of QoS parameters of 3.25 and included in the Good category according to TIPHON.